"Ee-taow!" the next chapter - Cross, John R.; Zook, Mark.; New Tribes Mission; Destination Summit/ Media (Sanford, Fla. : New Tribes Mission, 1993)
The continuing story of how the Mouk tribe of Papua New Guinea has responded to the Gospel of Jesus Christ, interspersed with interviews of missionary Mark Zook by John Cross.
Production managers, Diane Askew, Missy Beltran, Dave Ducommun ; edited by Dan Huntting, Missy Beltran ; music, Miller Goodman ; videography, Dan Huntting, Gary Roberts.
VHS Hi-Fi stereo.
Keywords: Zook, Mark; Missions -- Papua New Guinea; Mouk (Papua New Guinean people) -- Religion; Church development, New